Physical Activity Drops During Summer Holidays for 6- to 9-Year-Old Children - Volmut, Tadeja; Pišot, Rado; Planinšec, Jurij; Šimunič, Boštjan (Frontiers in Public Health, 2021)
Regular physical activity (PA) reduces the health risk of childhood obesity and associated chronic diseases as well as mental health problems. Since PA declines as children age as well with future generations it is of highest importance to intervene in school and out-of-school settings. Out-of-school periods affect children’s PA as it is mainly left to the interest and motivation of their parents. We compared accelerometer-based PA patterns in 93 six- to nine-year old children assessed four times: before (May/June), during (August) and after (September) summer holidays and at a 1-year follow up (May/June). Before summer holidays children were assessed also for anthropometry and motor tests. During summer holidays overall PA decreased by 18 % (p<0.001), physical inactivity increased by 5.5 % (p<0.001), moderate PA decreased by 53 % (p<0.001) and moderate to vigorous PA decreased by 45 % (p<0.001) when compared to before summer holidays. Furthermore, overall PA remained diminished also after summer holidays by 8.8 % (p=0.001) but recovered to baseline values at 1-year follow up. About 30 % of overall PA and moderate to vigorous PA decrease during summer holidays could be explained by children’s fitness level as a greater decrease was found in children with better results in standing long jump and 300-metre running time. Our finding detects an alarming summer holiday decrease in children PA that should not be neglected in future studies and intervention designs.